0960 Interactive Associations of Obstructive Sleep Apnea and Hypertension with longitudinal changes in β-Amyloid Burden and Cognitive Decline in Clinically Normal Elderly Individuals. (12th April 2019) - Bubu, Omonigho M; Andrade, Andreia; Parekh, Ankit; Kam, Korey; Mukhtar, Fahad; Donley, Tiffany; Seixas, Azizi A; Varga, Andrew; Ayappa, Indu; Rapoport, David; Forester, Terrence; Jean-Louis, Giradin; et al.
Abstract: Introduction: We determined whether the co-occurrence of OSA and hypertension interact synergistically to promote β-Amyloid burden and cognitive decline in clinically normal older adults Methods: Prospective longitudinal study utilizing NYU cohort of community-dwelling cognitively-normal elderly, with baseline and at least one follow-up of CSF-Aβ42 (measured using ELISA), and neuropsychological visits. OSA was defined using AHI4%. Hypertension diagnosis was according to AHA-guidelines. Cognitive variables assessed included Logic-2, Animal-Fluency [AF], Vegetable-Fluency [VF]), Boston-Naming-Test [BNT], Digit-Symbol-Substitution-Test [DSST], Trails Making Test-A and B [TMT-A and B]). Linear mixed-effects models with random intercept and slope were used to assess associations between OSA, hypertension, and longitudinal changes in CSF-Aβ and cognition, controlling for age-at-baseline, sex, APOE4-status, years-of-education, and their interactions with time. Results: Of the 98 participants, 63 (64.3%) were women. The mean (SD) age was 69.6 (7.3) years and follow-up time was 2.46 (0.64) years. OSA and hypertension were each associated with faster rate-of-change in CSF-Aβ42 (β = -3.11; 95%CI, −3.71, −2.51; and β= -2.82, 95% CI -3.29, -2.35, P < .01 for both respectively). The interaction of OSA and hypertension with time was significant (β= -1.28, 95% CI -1.78 to -0.78, P < .01) suggesting a synergistic effect. No significant associations were seen between annual-changes in CSF-Aβ42 and cognitive-decline. However, faster decline in VF, and DSST were associated with OSA (β = −0.054; 95%CI, −0.094, −0.013; P = .02; β = −0.058; 95%CI, −0.084, −0.033; P < .05 for both respectively), and with hypertension (β = −0.048; 95%CI, −0.079, −0.017; P = .04; β = −0.078; 95%CI, −0.098, −0.057; P = .002; respectively). The interaction of OSA and hypertension with time was significant for both VF and DSST (β = −0.033, 95%CI, −0.048, −0.018; P < .001 and β = −0.040, 95%CI, −0.064, −0.016; P < .001, respectively), suggesting a synergistic effect. Conclusion: In cognitive-normal elderly OSA individuals, vascular risk may complement AD-biomarkers in assessing risk of prospective cognitive-decline in preclinical AD. Support (If Any): NIH/NIA/NHLBI-T32HL129953, RO1AG056031, R01HL118624, and K07AG052685